Quasi-experimental evidence on the effect of traffic externalities on housing prices - Ioulia Ossokina; Gerard Verweij (European Regional Science Association (ERSA), 2011)
This paper studies the effects on house prices of traffic nuisance on local streets. As source of exogenous variation in traffic nuisance we use the opening of a new state highway N14 in the Netherlands. This transport innovation altered the traffic density on the adjacent streets for some households, but left others unaffected. Controlling for spatial and house heterogeneity, we find that doubling of traffic density reduces housing prices with about 2%, what implies an upper value of traffic noise discount of about 0.5% per decibel. Our results indicate further that traffic nuisance discounts are likely to be misestimated in cross-sectional studies because nuisance tends to be correlated with omitted neighbourhood and housing amenities.
Keywords: 330